Chemical Sensor Based on a Hollow-Core Photonic Crystal Fiber - Mansour, Tahreer S.; Abbass, Dalia H. (Iraqi Journal of Laser, 2019)
In this work a chemical sensor was built by using Plane Wave Expansion (PWE) modeling technique by filling the core of 1550 hollow core photonic crystal fiber with chloroform that has different concentrations after being diluted with distilled water. The minimum photonic bandgap width is.0003 and .0005 rad/sec with 19 and 7 cells respectively and a concentration of chloroform that filled these two fibers is 75%.